Diabetes Treatment Satisfaction on Hospital Outcome through Patient Empowerment - Tjiptabudi, Vitta; Antonio, Ferdi (Jurnal Kesehatan Masyarakat, 2025)
This study examines the relationship between Patient Satisfaction with Diabetes Treatment and Hospital Reputation, with Patient Empowerment and Well-being acting as mediators. Additionally, this study includes Lifestyle as the moderating component. This quantitative, cross-sectional study employs a survey methodology using a structured questionnaire of respondents selected by quota sampling. A total of 160 respondents were obtained from two private hospitals. Data was analyzed using Partial Least Square Structural Equation Modelling (PLS-SEM). Diabetes Treatment Satisfaction is assessed as a higher-order construct (HOC) consisting of dimensions of Patient Empowerment as a lower-order construct (LOC). The three LOCs are Patient Control, Patient Participation, and Patient Support. This study employs a disjoint two-step methodology. The research findings indicate a strong and positive relationship between Diabetes Treatment Satisfaction and Hospital Reputation mediated by Patient Empowerment and Patient well-being. The indirect effect is statistically significant (p-value < 0.05, CI 95%). The analysis also reveals a strong relation between Patient Well Being and Hospital Reputation (β=0.842, f2=2.427). However, the Lifestyle variable did not substantially relate to the relationship between Diabetes Treatment Satisfaction and Patient well-being. This study model has been empirically validated to provide sufficient explanatory and predictive capacities for assessing hospital reputation.